A phosphoinositide switch mediates exocyst recruitment to multivesicular endosomes for exosome secretion - Liu, Di-Ao; Tao, Kai; Wu, Bin; Yu, Ziyan; Szczepaniak, Malwina; Rames, Matthew; Yang, Changsong; Svitkina, Tatyana; Zhu, Yueyao; Xu, Fengyuan; Nan, Xiaolin; Guo, Wei (Nature communications, 2023)
Exosomes are secreted to the extracellular milieu when multivesicular endosomes (MVEs) dock and fuse with the plasma membrane. However, MVEs are also known to fuse with lysosomes for degradation. How MVEs are directed to the plasma membrane for exosome secretion rather than to lysosomes is unclear. Here we report that a conversion of phosphatidylinositol-3-phosphate (PI(3)P) to phosphatidylinositol-4-phosphate (PI(4)P) catalyzed sequentially by Myotubularin 1 (MTM1) and phosphatidylinositol 4-kinase type IIα (PI4KIIα) on the surface of MVEs mediates the recruitment of the exocyst complex. The exocyst then targets the MVEs to the plasma membrane for exosome secretion. We further demonstrate that disrupting PI(4)P generation or exocyst function blocked exosomal secretion of Programmed death-ligand 1 (PD-L1), a key immune checkpoint protein in tumor cells, and led to its accumulation in lysosomes. Together, our study suggests that the PI(3)P to PI(4)P conversion on MVEs and the recruitment of the exocyst direct the exocytic trafficking of MVEs for exosome secretion. The molecular mechanism by which exosomes are released from cells is unclear. Here the authors report that a phosphatidylinositide conversion couples the recruitment of the octameric exocyst complex to multivesicular endosomes for exosome secretion.